Comment on “Confucian heresy and religious imagination: a study of the renderings of Mozi by protestantism missionaries in 19th century” - Ma, Ji (2024)
Commented Article: LIN, Jiaxin; YU, Zihan; HU, Honghui. Confucian Heresy and Religious Imagination: A Study of the Renderings of Mozi by Protestantism Missionaries in 19th Century. Trans/Form/Ação: Unesp Journal of Philosophy, v. 47, n. 4, e0240044, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14633.